2012
DOI: 10.1002/mats.201200055
|View full text |Cite
|
Sign up to set email alerts
|

Computer Study of the Association Behavior of Gradient Copolymers: Analysis of Simulation Results Based on a New Algorithm for Recognition and Classification of Aggregates

Abstract: We present a computer study of the association behavior of copolymer chains with a gradient part and soluble tail of variable length. As a simulation method we use dynamic Monte Carlo simulation on a simple cubic lattice with pair interaction parameters. The solvent quality and selectivity is modeled by the variation of pair interaction parameters between nearest neighbors on the lattice. The role of the length of soluble part in the self‐assembly and its effect on the structure of aggregates was the main goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…Specifically, some of the solvophilic units may be integrated in the core while some solvophobic units may be distributed in the corona. Thus, GCs usually possess greater solubility than the corresponding BCs [18,20,21], slower micellization process [22] and a lower value of the aggregation number [19,23], reflecting a smaller size according to DLS [24].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, some of the solvophilic units may be integrated in the core while some solvophobic units may be distributed in the corona. Thus, GCs usually possess greater solubility than the corresponding BCs [18,20,21], slower micellization process [22] and a lower value of the aggregation number [19,23], reflecting a smaller size according to DLS [24].…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, computer simulations have recently made substantial strides 4,19,20,21,22,23,24,25,26,27,28,29,30,31 focusing on solutions of linear multiblock copolymers of the (A n B n ) m type, where n is the degree of polymerization of each block and m is the number of blocks. Systematic explorations within the large parameter space established quantitative relations on how copolymer architecture and intermolecular interactions determine the macroscopic phase behavior and the related chain conformations changes.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies of the association behaviour of gradient copolymers in selective solvents have been reported over the past few years [98,99,105,164,204,[219][220][221][222][223][224][225][226]. A significant finding was that gradient copolymers have higher solubility than the corresponding diblock copolymers leading to significantly higher values of the CMC [173,222,227].…”
Section: Micellization and Solution Propertiesmentioning
confidence: 99%
“…A significant finding was that gradient copolymers have higher solubility than the corresponding diblock copolymers leading to significantly higher values of the CMC [173,222,227]. Monte Carlo (MC) simulations have been employed to study the self-assembly of gradient copolymers, which differs with respect to the steepness of the gradient of the local composition along the chain [225]. It was demonstrated that the association behaviour does not depend solely on the net composition of the copolymers, but also on the sequence of monomer units [228].…”
Section: Micellization and Solution Propertiesmentioning
confidence: 99%
See 1 more Smart Citation